PENINGKATAN KETERAMPILAN MENGGUNAKAN PERALATAN BENGKEL KAYU MELALUI PELATIHAN PEMBUATAN RAK SANDAL - sukania, i wayan sukania; Teresa Novita; Kezia Samosir (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2024)
ABSTRACT Skills improvement training is a manifestation of Untar's role in the community around the campus. SMKN 12 Tangerang Banten is the right PKM partner considering that this school has not provided subject matter on product design, even in the motorcycle engineering and business majors. This results in a lack of knowledge, understanding and skills of students in product design and manufacturing activities. Additional knowledge and skills are needed by graduates to be more competitive and creative. The students' interest in participating in the training is very high, therefore the training in designing and manufacturing sandal rack products made of plywood is expected to be able to meet the needs of the participants. Phase 1 activities on Saturday, May 11, 2024, in the form of an explanation of marketing theory, product design and ergonomics as well as an explanation of product design case examples. Participants learn to design products according to the requirements given. Phase 2 activities are practice in a wood workshop on Sunday, May 12, 2024. The elements of work carried out are measuring, cutting, planing, sanding, assembling, and painting the sandal rack products made. Based on the questionnaire, it is known that there was a 27% increase in understanding the role of marketing research and human factors in designing a product, a 20% increase in understanding the stages of product design, a 47% increase in understanding the use of work equipment in the workshop, 100% of participants said that the instructor's guide was easy to understand, 100% said the training implementation method was satisfactory, and as many as 87% of participants gave positive comments. In general, through the provision of theory, insight and practice in the workshop, the product design abilities and work skills of the participants increased. ABSTRAK Pelatihan peningkatan keterampilan merupakan perwujudan peran Untar kepada masyarakat sekitar kampus. SMKN 12 Tangerang Banten merupakan mitra PKM yang tepat mengingat sekolah ini belum memberikan materi pelajaran mengenai perancangan produk, bahkan pada jurusan teknik dan bisnis sepeda motor. Hal ini mengakibatkan minimnya pengetahuan, pemahaman dan keterampilan para siswa pada kegiatan perancangan dan pembuatan produk. Pengetahuan dan keterampilan tambahan sangat diperlukan oleh para lulusan agar lebih mampu bersaing dan berkarya. Minat para siswa mengikuti pelatihan sangat besar, oleh karena itu pelatihan perancangan dan pembuatan produk rak sandal berbahan kayu lapis diharapkan mampu menjawab kebutuhan peserta. Kegiatan tahap 1 pada Sabtu tgl 11 mei 2024, berupa pemaparan teori pemasaran, perancangan produk dan ergonomi serta pemaparan contoh kasus perancangan produk. Para peserta belajar merancang produk sesuai persyaratan yang diberikan. Kegiatan tahap 2 yaitu praktik di bengkel kayu pada hari Minggu tgl 12 Mei 2024. Elemen pekerjaan yang dilakukan yaitu mengukur, memotong, menyerut, mengamplas, merakit, dan mengecat produk rak sandal yang dibuat. Berdasarkan kuesioner diketahui bahwa terjadi peningkatan sebesar 27% pada pemahaman perananan riset pemasaran dan faktor manusia dalam perancangan sebuah produk, kenaikan 20% pada pemahaman tahapan perancangan produk, kenaikan 47% pada pemahaman penggunaan peralatan kerja di bengkel, 100% peserta mengatakan bahwa panduan instruktur mudah dipahami, 100 % mengatakan metode pelaksanaan pelatihan memuaskan, dan sebanyak 87% peserta memberikan komentar positif. Secara umum melalui pembekalan teori, wawasan dan praktik di bengkel kerja, kemampuan perancangan produk dan keterampilan kerja para peserta meningkat.